Mythic Prostitutes, AIDS and Criminal Law - Kane, Stephanie (Ethnologies, 2001)
Three key cases in the legal front against hiv-positive prostitutes in the United States demonstrate the ease with which individual malice or desperation can be amplified to condemn a whole category of marginalised persons. Ethnographic and epidemiologic resources, supplemented by the imagined subjective perspectives of the voiceless women in question, are drawn into textual analysis of legal and mass mediated case reports to identify the pragmatic and ethical implications of the government’s shadow approach to AIDS intervention.